Restructuring federal climate research to meet the challenges of climate change [electronic resource] (National Academies Press, 2009)
With effective climate change mitigation policies still under development, and with even the most aggressive proposals unable to halt climate change immediately, many decision makers are focusing unprecedented attention on the need for strategies to adapt to climate changes that are now unavoidable. The effects of climate change will touch every corner of the world's economies and societies; adaptation is inevitable. The remaining question is to what extent humans will anticipate and reduce undesired consequences of climate change, or postpone response until after climate change impacts have altered ecological and socioeconomic systems so significantly that opportunities for adaptation become limited. This book summarizes a National Research Council workshop at which presentations and discussion identified specific needs associated with this gap between the demand and supply of scientific information about climate change adaptation